2009
DOI: 10.1002/glia.20902
|View full text |Cite
|
Sign up to set email alerts
|

Axons and astrocytes release ATP and glutamate to evoke calcium signals in NG2‐glia

Abstract: NG2-glia are an abundant population of cells in the adult CNS that make up a novel glial cell type. Here, we have examined calcium signals in NG2-glia identified by expression of the fluorescent protein DsRed under the control of the NG2 promoter in the white matter of the mouse optic nerve. We focused on mice aged postnatal day (P)12-16, after the main period of oligodendrocyte generation. Using fluo-4 and fura-2 calcium imaging in isolated intact nerves, we show that glutamate and ATP evoke Ca(2+) signals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(163 citation statements)
references
References 45 publications
5
157
1
Order By: Relevance
“…The first in vivo evidence that, upon release during axonal action potential, ATP evokes rapid and transient Ca 2þ rises in single OPCs was attested by confocal calcium imaging on optic nerves from a transgenic reporter mouse line in which adult NG2-glia were identified by the expression of the red fluorescent protein DsRed [85]. The predominant mechanism was the activation of metabotropic P2Y 1 R, because response was abolished by the pre-incubation with the P2Y 1 R antagonist MRS2179, but also the P2X7R induced significant calcium increases [85].…”
Section: Oligodendroglial Precursor Cells (Ng2-glia)mentioning
confidence: 99%
See 2 more Smart Citations
“…The first in vivo evidence that, upon release during axonal action potential, ATP evokes rapid and transient Ca 2þ rises in single OPCs was attested by confocal calcium imaging on optic nerves from a transgenic reporter mouse line in which adult NG2-glia were identified by the expression of the red fluorescent protein DsRed [85]. The predominant mechanism was the activation of metabotropic P2Y 1 R, because response was abolished by the pre-incubation with the P2Y 1 R antagonist MRS2179, but also the P2X7R induced significant calcium increases [85].…”
Section: Oligodendroglial Precursor Cells (Ng2-glia)mentioning
confidence: 99%
“…The predominant mechanism was the activation of metabotropic P2Y 1 R, because response was abolished by the pre-incubation with the P2Y 1 R antagonist MRS2179, but also the P2X7R induced significant calcium increases [85]. The Ca 2þ signals increased in both amplitude and duration with increasing stimulus strength, indicating that responses in these cells matched with axonal activity; however, it was clearly demonstrated that ATP is not only released by axons during action potentials, but also comes from astrocytes, in response to axonal activity through vesicles, reverse transport, hemichannels and the P2X7R [86].…”
Section: Oligodendroglial Precursor Cells (Ng2-glia)mentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ATP release significantly increases process extension toward an injury site for resting or activated microglia [148]. Astrocytes under pathological conditions also can release ATP to activate P2Rs in neighboring cells [18,188,189], and inflammation in vivo can elevate extracellular ATP levels sufficiently to activate P2 receptors [18].…”
Section: Glial-neuronal Interactions Involving P2y 2 Receptorsmentioning
confidence: 99%
“…OPC express all four subunits, although GluA1 represents a minor contributor compared with GluA2–4 in vitro (Hossain, Liu, Fragoso, & Almazan, 2014; Itoh et al, 2002), and appears to be entirely absent from OPC in vivo (Kougioumtzidou et al, 2017). Activation of OPC AMPAR provokes an influx of Ca 2+ (Ge et al, 2006; Haberlandt et al, 2011; Hamilton, Vayro, Wigley, & Butt, 2010; Itoh et al, 2002) that can mediate excitotoxic injury in vitro (Alberdi, Sanchez‐Gomez, Marino, & Matute, 2002; Deng, Rosenberg, Volpe, & Jensen, 2003; Li & Stys, 2000; Sanchez‐Gomez & Matute, 1999). These observations suggest that a substantial number of OPC AMPAR lack GluA2 subunits since inclusion of this subunit limits the permeability of AMPAR to Ca 2+ (Geiger et al, 1995; Hollmann, Hartley, & Heinemann, 1991).…”
Section: Introductionmentioning
confidence: 99%